1994
DOI: 10.1029/94gl00694
|View full text |Cite
|
Sign up to set email alerts
|

Transient electric signals prior to rock failure under uniaxial compression

Abstract: Transient variations of the electric field are detected, prior to the failure of a rock sample which is subjected to uniaxial compression at a variable rate. These precursory electric signals are attributed to the stress induced polarization of the sample and seem to have a form similar to the so called Seismic Electric Signals (SES), which are detected in Greece by the VAN network, prior to earthquakes. The emitted electric signals seem to follow in form the variations of the first time derivative of the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…It would even be consistent with the view that the amount of electric current density at the source would have to be unrealistically huge for SES to travel hundreds of km in a homogeneous medium. Simple calculation indicated that 10 -9 A/cm 2 , which is compatible with laboratory data (Hadjicontis and Mavromatou 1994), would suffice if the observation site and focal area are connected by a narrow conductive channel. One interesting feature of the selectivity map discovered by us ) is that it changes with time: the EQ source mechanism in Kefallinia region changed from a strike-slip type to thrust type in late 1987 and this coincided with a shift in the sensitive site from PIR station to IOA station.…”
Section: Selectivity: (How To Predict An Epicenter)mentioning
confidence: 74%
“…It would even be consistent with the view that the amount of electric current density at the source would have to be unrealistically huge for SES to travel hundreds of km in a homogeneous medium. Simple calculation indicated that 10 -9 A/cm 2 , which is compatible with laboratory data (Hadjicontis and Mavromatou 1994), would suffice if the observation site and focal area are connected by a narrow conductive channel. One interesting feature of the selectivity map discovered by us ) is that it changes with time: the EQ source mechanism in Kefallinia region changed from a strike-slip type to thrust type in late 1987 and this coincided with a shift in the sensitive site from PIR station to IOA station.…”
Section: Selectivity: (How To Predict An Epicenter)mentioning
confidence: 74%
“…In bibliography it has been observed that when mechanical stress is applied upon a rock sample it reacts by emitting electric current (Brady and Rowell, 1986;Enomoto and Hashimoto, 1990;Hadjicontis and Mavromatou, 1994;Takeuchi and Nagahama, 2001;Freund, 2002;Stavrakas et al, 2003). Numerous laboratory experiments including many fracture tests have been conducted on various minerals and rocks both dry and saturated in order to understand and interpret the nature of the mechanisms responsible for the production of such electrical signals (Yoshida et al, 1998;Vallianatos et al, 2004;St-Laurent et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that the recombination rate of the sample's separated charges is clearly larger than the stress variations rate. As far as the origin of the sample's electric polarization (due to the stress variations) is concerned, it could be attributed either to the well known piezoelectric effect, if the sample has piezoelectric properties (granite, quartzite), or to the movements of segments of charged dislocations with respect to their compensating Debye-Hückel cloud of point defects, if the sample is not piezoelectric, (pure LiF) (Hadjicontis and Mavromatou, 1994). We must take under consideration that the stress field within the sample is inhomogeneous.…”
Section: Stress Induced Polarization Currentsmentioning
confidence: 99%
“…Enough cases of laboratory experiments are reported in the literature (Enomoto and Hasimoto, 1990;Hadjicontis and Mavromatou, 1994;Freund, 2002;Khatiashvili and Perelman, 1989;Mogi, 1962;Nitsan, 1977;Ogawa et al, 1985;Yamada et al, 1982;Warwick, 1982). Although various aspects, that satisfactorily explain the generation mechanisms of an earthquake, have been suggested so far, it cannot be maintained that the special conditions and processes…”
Section: Introductionmentioning
confidence: 99%